2009
DOI: 10.1158/1078-0432.ccr-09-0312
|View full text |Cite
|
Sign up to set email alerts
|

Subsets of Very Low Risk Wilms Tumor Show Distinctive Gene Expression, Histologic, and Clinical Features

Abstract: Purpose: Recent studies suggest that children <24 months with stage I favorable histology Wilms tumors <550 g [very low risk Wilms tumors (VLRWT)] have an excellent prognosis when treated with nephrectomy only, without adjuvant chemotherapy. The identification of risk categories within VLRWT may enable refinement of their definition and optimization of their therapy. Experimental Design: To define biologically distinct subsets, global gene expression analysis was done on 39 VLRWT that passed all quality-contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…In one patient with MayerRokitansky-Kuster-Hauser syndrome showing bilateral multicystic dysplastic kidneys a microdeletion at chromosome 17q12 has been detected that includes among role of LIM1 in the pathogenesis of nephroblastomas has not been investigated in detail to date. Microarray analysis of a xenograft model of nephroblastomas [28] and an additional microarray analysis of various subtypes of primary nephroblastomas indicated that overexpression of LIM1 might play a role in their pathogenesis [13,28] . In our series of various subtypes of nephroblastomas only 1 of 12 samples with LIM1 expression showed diffuse staining in tubular structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one patient with MayerRokitansky-Kuster-Hauser syndrome showing bilateral multicystic dysplastic kidneys a microdeletion at chromosome 17q12 has been detected that includes among role of LIM1 in the pathogenesis of nephroblastomas has not been investigated in detail to date. Microarray analysis of a xenograft model of nephroblastomas [28] and an additional microarray analysis of various subtypes of primary nephroblastomas indicated that overexpression of LIM1 might play a role in their pathogenesis [13,28] . In our series of various subtypes of nephroblastomas only 1 of 12 samples with LIM1 expression showed diffuse staining in tubular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factors that are active during renal development have also been found to be reactivated in nephroblastomas. These include HMGA2 (high mobility group AT-hook 2) [13] , CITED1 [2] and PAX2 [3] . Despite the already described overexpression of PAX2 in nephroblastomas in blastema and some epithelial structures by in situ hybridization [3] and in the epithelial component by Western blot and immunohistochemistry [27] , surprisingly the Additionally, we evaluated more common renal neoplasms, clear cell carcinomas and papillary cell carcinomas of the kidney, for expression of LIM1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case study we consider the GSE14767 gene expression dataset [35] from the GEO repository comprising 39 microarray measurements of Wilms tumor samples. A Wilms tumor is a kind of kidney cancer which mainly affects children and contains metanephric blastema.…”
Section: Case Studymentioning
confidence: 99%
“…Tumors with a high level of epithelial differentiation (EDT) have been reported to be associated with very good survival rates. On the other hand tumors containing higher amounts of metanephric blastema (blastemal tumors) have a much worse prognosis with a 79% chance of the tumor reappearing after four years [35]. Here we want to study the differences between blastemal tumors as sample and EDT as reference group.…”
Section: Case Studymentioning
confidence: 99%